Vulvar lymphangioma circumscriptum in an adolescent. A case report - Urbina, Claudia (2020)
We report the case of a 13-year-old patient with no previous medical history who presented multiple verrucous, papular and hyperkeratotic lesions on the labia majora of the vulva of one year of evolution, occasional bleeding and skin hyperpigmentation. Histopathology of the vulvar biopsy confirmed the diagnosis of vulvar lymphangioma. This entity is a benign and rare alteration of lymph vessels and, although it can occur anywhere on the skin surface, it is most commonly found in chest, thighs and buttocks. Vulvar presentation is rare. It is considered to account for less than 6% of benign childhood tumors.